Farmers' awareness of digital credit: Does financial literacy matter? - Yaw Sarfo; Oliver Musshoff; Ron Weber (Journal of International Development, 2023)
This study investigates the relationship between financial literacy and farmers' awareness of digital credit in rural Madagascar. We apply questions that demonstrate individuals' understanding of the four fundamental concepts for financial decision making: numeracy, interest compounding, inflation and risk diversification to measure farmers' financial literacy. We find that financial literacy has a positive and statistically significant effect on farmers' awareness of digital credit. Our study highlights the importance of financial literacy for increasing farmers' awareness of digital credit in rural areas of Madagascar and supports the widely held view that financial literacy is crucial for individuals' awareness of financial products.
Keywords: 300; awareness of financial products; digital credit; financial literacy; Madagascar; smallholder farmers